STRATEGI PENGEMBANGAN MASJID BAGI GENERASI MUDA - Basit, Abdul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Abstract: An effort to develop young generation is a must and became urgent necessity. This huge project needs participation fromall elements, especially ta’mir (management) masjid. With total 700.000 Masjid in Indonesia, if it can optimally develop younggeneration, it can promise successfulness. Therefore, we need a policy and support so that masjid can intensify its program to younggeneration. There are two strategies to develop young generation: internal-personal strategy and external-institutional strategy.Strategy internal-personal oriented to understanding and application of Islamic teaching to youth, whereas external-institutionalstrategy oriented to empowering youth’s organization